Antimicrobial Susceptibility Pattern in Blood Culture at Chattogram - Salsabil Ripa, Sabira; Sultana, Kawsar; Mokarrama, Moniat (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Blood stream infection is a predominant cause of morbidity and mortality in Bangladesh and needs urgent treatment with antimicrobial drugs. Blood culture is the gold standard for the diagnosis of blood infection. Patient's final outcome might be improved with detailed and organized surveillance studies on bloodstream isolates and their resistance. The present study deals with the isolation of blood culture isolates from patients of a hospital in Chattogram,Bangladesh and their antibiotic susceptibility pattern. Materials and methods: A purposive cross sectional retrospective study was conducted with a total 100 suspected bacteremia patients in 6 months duration in different lab of Chattogram to determine bacteriological profile of blood culture and antibiogram of the isolates. Bacterial isolates and their antibiotic sensitivity test were done according to standard microbiological techniques. Results: Approximately 53% of the cases are female and 75% in the under 5 years of age group. 36% of the culture isolates were Acinetobacter and other common isolates were Klebsiella (22%), Pseudomonas (18%), Salmonella typhi (17%), Staphylococcus aureus (4%), E.coli (3%). However, all the tested isolates were found mostly sensitive against Vancomycin, Gentamycin, Tazobactum. Penicillin had the highest overall resistance of (100%), followed by Ampicillin (100%) and Ceftazidime (90%). Cefepime, Cefuroxime, Cefixime, had overall resistance rates of 89%, 85%, 83% respectively. Highest drug resistance was found with Ampicillin (100%) and Penicillin (100%) against Acinetobacter. There were no isolates completely resistant to all the antibiotics tested. Conclusion: This study highlights that surveillance detection of causative agents of blood stream infections and their antibiogram should be done regularly in the hospital.We expect our present work will be helpful for the healthcare professionals to provide improved treatment. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 67-71